2022
DOI: 10.54536/ajaset.v6i2.441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Mobility of COVID-19 Epidemic in Kuala Lumpur using GIS

Abstract: During the third COVID-19 wave in Malaysia, the Ministry of Health suggested a complete lockdown (Movement Control Order-MCO). However, tracking people's movements would help curb the virus' spread. Movement data helps companies uncover human mobility patterns, analyse present and previous movement patterns, and anticipate future consequences. GIS can generate flow maps, themed maps, and flow charts. GIS can show people moving from one site to another and study the link between people moving and land usage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The six million people moving out of the Klang Valley and Negeri Sembilan also worries the Malaysian Ministry of Health (MOH), who fear that this could result in an increase in COVID-19 cases in the US. The majority of districts in Selangor, Kuala Lumpur, and Putrajaya, according to him, are now COVID-19 red zones, and it would be difficult to impose restrictions on the movement of people in these densely populated areas (Malymail, 2020) By zoning Kuala Lumpur city into subzones and using a covid-19 outbreak data and human movement data, we found that in the same period (RMCO) from December 1, 2020, and January 15, 2021, Bukit Bintang area recorded the most significant number of cases with 3555 cases, in addition, it ranked as the most visited places (Qwasmi et al, 2022) Produced layers and collected data had to be processed and transformed into the proper format before they could be used for analysis. Data preparation is required since most received data were initially received as pictures and cannot be used right away and because most GIS applications need some raster data to be georeferenced.…”
Section: Justification Of Site Selectionmentioning
confidence: 93%
See 3 more Smart Citations
“…The six million people moving out of the Klang Valley and Negeri Sembilan also worries the Malaysian Ministry of Health (MOH), who fear that this could result in an increase in COVID-19 cases in the US. The majority of districts in Selangor, Kuala Lumpur, and Putrajaya, according to him, are now COVID-19 red zones, and it would be difficult to impose restrictions on the movement of people in these densely populated areas (Malymail, 2020) By zoning Kuala Lumpur city into subzones and using a covid-19 outbreak data and human movement data, we found that in the same period (RMCO) from December 1, 2020, and January 15, 2021, Bukit Bintang area recorded the most significant number of cases with 3555 cases, in addition, it ranked as the most visited places (Qwasmi et al, 2022) Produced layers and collected data had to be processed and transformed into the proper format before they could be used for analysis. Data preparation is required since most received data were initially received as pictures and cannot be used right away and because most GIS applications need some raster data to be georeferenced.…”
Section: Justification Of Site Selectionmentioning
confidence: 93%
“…The initial need of the accessibility element is connectivity. The sidewalk centerline vector data from the Bukit Bintang region sidewalk were taken from (Qwasmi et al, 2022) figure, which was used to assess connectivity ( 9). This research is counting the number of actual intersections in the sidewalk and excluding pedestrianinaccessible street crossings on highways.…”
Section: Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2: Kuala Lumpur cases by districts as of February 7, 2021 (source MOH 2021) By zoning Kuala Lumpur city into sub-zones and using a covid-19 outbreak data and human movement data, we found that in the same period (RMCO) from December 1, 2020, and January 15, 2021, Bukit Bintang area recorded the most significant number of cases with 3555 cases, in addition, It ranked as the most visited places Figure (3)(Qwasmi et al, 2022) . Bukit Bintang is the retail and…”
mentioning
confidence: 98%